2022
DOI: 10.1002/pen.26172
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral capacity of polypropylene/(1‐Hexadecyl) trimethyl‐ammonium bromide composites against COVID‐19

Abstract: During the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic, scientists from different areas are looking for alternatives to fight it. SARS‐CoV‐2, the cause of the infectious respiratory disease COVID‐19, is mainly transmitted through direct or indirect contact with infected respiratory droplets. The integrity of the virus structure is crucial for its viability to attack human cells. Quaternary ammonium salts are characterized by having antiviral capabilities which alter or destroy the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…AgNPs possess a solid affinity for bacterial cell surfaces and can penetrate microbial bodies, eventually converting to silver ions (Ag + ) within the cytoplasm to disrupt intracellular structures 33–35 . Many other studies can be found on literature regarding the antiviral capacity against COVID‐19 36–40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AgNPs possess a solid affinity for bacterial cell surfaces and can penetrate microbial bodies, eventually converting to silver ions (Ag + ) within the cytoplasm to disrupt intracellular structures 33–35 . Many other studies can be found on literature regarding the antiviral capacity against COVID‐19 36–40 …”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Many other studies can be found on literature regarding the antiviral capacity against COVID-19. [36][37][38][39][40]…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Currently, natural virus inhibitors, metals/metal oxides/particles or ions, metal–organic frameworks, small organic molecules, salts, and carbon-based materials have been added to air filters to inactivate viruses or bacteria retained by filtration. In addition, researchers have systematically reviewed the current development of antiviral masks in terms of effectiveness, importance, preparation process, testing, and characterization, environmental impact, and development trend .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that bacteria Escherichia coli and Staphylococcus aureus are also able to survive on thermoplastic substrates 18 . Therefore, the incorporation of antimicrobial agents into polymeric materials can enhance their performance in preventing bacteria or viruses from surviving or proliferating on surfaces 19–23 …”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, the incorporation of antimicrobial agents into polymeric materials can enhance their performance in preventing bacteria or viruses from surviving or proliferating on surfaces. [19][20][21][22][23] Among the possible antimicrobial agents, some essential oils based on cinnamon, clove, thyme, oregano, eucalyptus, copaiba, green tea, rosemary pepper, among others can be mentioned. These agents have known antimicrobial substances, such as thymol, carvacrol, eugenol, β-caryophyllene, cinnamaldehyde, and so on.…”
mentioning
confidence: 99%